DEGRADATION OF SOME POLYSTRENE USING BEETLE LARVAE (TENEBRIO MOLITOR L.) - Ichsan Luqmana Indra Putra; Alfi Nurcahyasari (Universitas Medan Area, 2021)
One alternative to waste processing polystyrene is to use Tenebrio molitor larvae. This study aims to determine the increase in body length and weight, rate of degradation, and value of Waste Reduction Index (WRI) of larvae T. molitor. This study used laboratory experimental using completely randomized design experimental design model (CRD) data analysis with control and 4 feed treatments. Each treatment level was repeated 5 times in order to obtain 25 experimental units. Larvae were reared in a plastic container containing 10 larvae. Each larvae were given bran feed for control and polystrene for treatment, each feed as much as 1 gram. The polystyrene used were food packaging, walls, electronic packaging, and ice boxes. Larvae were measured for length and body weight every 3 days for 30 days. Parameters observed were increase in length and weight of larvae, rate of degradation and WRI values.The highest mean value of increase in larval length on the polystrene wall was 1.69 cm. The lowest value was polystyrene food packaging (1.59 cm). The average weight gain of larvae has a uniform value in the control and treatment of 0.07 gr. The highest degradation rate and WRI values were polystyrene wall and electronic packaging at 0.019 and 0.63%. while the lowest values were polystyrene food packaging at 0.11 and 0.37%.